Brazilian government violates Indigenous rights: What could induce a change? - Ferrante, Lucas; Martin Fearnside, Philip (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
The current presidential administration of Brazil has implemented a legislative agenda aimed at weakening protections of Indigenous peoples, in line with an ideological discourse and the direct participation of the armed forces in this process. This agenda has enabled invasions of Indigenous lands and a much higher COVID-19 mortality rate for Indigenous peoples when compared to non-Indigenous people. A bill recently approved by the Chamber of Deputies aims to extinguish all Indigenous lands established by the Brazilian government from 1988 onwards. This bill represents the official opening for violation of the rights of Indigenous peoples by the Bolsonaro administration and facilitates invasion of Indigenous lands. The president’s multiple efforts to weaken or deny protection of these peoples, to usurp their lands and to deny their rights to consultation on projects that affect them need to be judged by Brazil’s Federal Supreme Court, the UN Human Rights Council, the Inter-American Commission on Human Rights (IACHR), the Inter-American Court of Human Rights (IACtHR) and the International Criminal Court.